Present state of target therapy for disseminated renal cell carcinoma. (May 2010) - Waalkes, Sandra; Kramer, Mario; Herrmann, Thomas RW; Schrader, Andres J; Kuczyk, Markus A; Merseburger, Axel S
Both experimental and clinical researches focusing on advanced kidney cancer have increased continuously since the successful introduction of targeted therapy in the treatment of advanced metastatic renal cell carcinoma. Being refractory to conventional hormone therapy, chemotherapy or radiotherapy, renal cell carcinoma has become a model tumor for the development and evaluation of diverse novel targeted drugs. This review highlights currently available agents and summarizes evidence-based data regarding their effectiveness in metastatic renal cell carcinoma. Furthermore, the role of debulking tumor nephrectomy followed by systemic therapy as part of an optimum treatment algorithm is being elucidated.